Daily Life of Santri in Bone: An Ethnographic Study of Religious and Social Practices - Feby Triadi (Universitas Cahaya Prima, 2026)
This ethnographic study explores the daily life of santri in Bone Regency, examining how educational routines, religious practices, and social interactions shape values, identity, and community engagement. Using participant observation, in-depth interviews, and documentation of daily activities, the research investigates the ways in which pesantren foster discipline, religious knowledge, and social cohesion among santri. Findings indicate that daily life is structured around formal study, communal worship, mentoring relationships, and social responsibilities, reflecting both spiritual and cultural dimensions of pesantren education. The study highlights that pesantren function as educational institutions, moral frameworks, and community hubs, reinforcing the social and religious fabric of Bone Regency.